2020
DOI: 10.1016/j.psj.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incubation temperature pattern on broiler performance

Abstract: During incubation, development of embryos is affected by eggshell temperature ( EST ). A constant EST of 37.8°C has been considered so far to result in most optimal embryo development. However, it can be hypothesized that a higher EST in week 2 in combination with a lower EST in week 3 stimulates embryo development and subsequent grow-out performance. In this study, 468 eggs of a 44-week-old Ross 308 breeder flock were incubated at different incubation temperature patterns in a 2 × 2 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“… Maatjens et al (2016a) showed that a lower EST of 36.7°C from E15 onward resulted in chicks with a higher yolk-free body mass and a higher relative heart weight at hatch than an EST of 37.8°C. In the current experiment, no differences in yolk-free body mass were found when EST was lowered to 36.7°C in week 3 compared with a constant EST of 37.8°C ( Wijnen et al., 2020 ). Moreover, the current study found some indications that the lower temperature in the last week of incubation impaired organ maturation instead of improving embryo development.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“… Maatjens et al (2016a) showed that a lower EST of 36.7°C from E15 onward resulted in chicks with a higher yolk-free body mass and a higher relative heart weight at hatch than an EST of 37.8°C. In the current experiment, no differences in yolk-free body mass were found when EST was lowered to 36.7°C in week 3 compared with a constant EST of 37.8°C ( Wijnen et al., 2020 ). Moreover, the current study found some indications that the lower temperature in the last week of incubation impaired organ maturation instead of improving embryo development.…”
Section: Discussioncontrasting
confidence: 58%
“…The experimental protocol was approved by the Governmental Commission on Animal Experiments, the Hague, The Netherlands; approval number: 2016.W-0087.001. For further details about material and methods, please review Wijnen et al. (2020) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations